Chapter 14 The science of population and birth control in post-war Japan - Homei, Aya (Taylor & Francis, 2016)
This essay examines the entanglement between population science and population governance immediately after World War II. It analyzes debates on population and birth control research that contributed to the state-endorsed birth control campaign. Drawing on the existing works on the campaign as well as coproduction theory proposed in science and technology studies (STS), this essay depicts how the Japanese state's post-war birth control policy was coproduced with a particular kind of population science that insisted on the necessity of birth control for Japan's post-war reconstruction.